Analisis bibliometrik perkembangan penelitian halal food - Anam, Muhammad Syariful (Journal of Halal Industry Studies, 2022)
This study aims to determine the development of research on halal foods from 2004 to 2021. This study uses data from the Scopus database taken with Publish or Perish (PoP) software. After the data was downloaded, it was checked and refined using the Mendeley software, and the final result was 193 articles that were ready to be analyzed. This study uses a literature review method with bibliometric analysis using VOSviewer software. The analysis results show that the trend of research on halal food has increased every year. Furthermore, Suhaiza Zailani is a prolific writer who often collaborates on research with other writers. In addition, the articles about halal food that are most frequently cited are those written by Shah Alam and Mohamed Sayuti. Meanwhile, research on halal food with the subjects of "food security," "Muslim tourists," "motivation," "sustainability," and "pork" still has the opportunity to be researched in the future.